Can Discrepancies Between Coronary Computed Tomography Angiography and Cardiac Catheterization in High-Risk Patients be Overcome With Consensus Reading?. Issue 1 (January 2017) - Steinberger, Sharon; Plodkowski, Andrew J.; Latson, Larry; Levsky, Jeffrey M.; Zalta, Benjamin; Godelman, Alla; Cohen, Hillel W.; Haramati, Linda B.
Abstract : Objective: To assess the incidence and cause of discrepancies between coronary computed tomography angiography (CTA) and catheterization in a high-risk, diverse, predominantly overweight inner-city population. Methods: Ninety-two patients who underwent coronary CTA and catheterization on March 2007 to December 2012 were retrospectively identified. Clinical coronary CTA interpretation and reinterpretation by a review panel was compared with catheterization results. Results: Severe stenosis was present on catheterization in 65% (60/92). Clinical coronary CTA was concordant with catheterization for severe stenosis in 78% (72/92), whereas panel interpretation was concordant in 77% (70/91). Sensitivity and specificity of clinical and panel coronary CTA interpretations were 92% (55/60) and 53% (17/32) versus 82% (48/59) and 68% (22/32), respectively. Conclusions: Both coronary CTA interpretations were concordant with catheterization for severe stenosis in three quarters of patients. However, the diagnostic profile of the 2 interpretations differed, with higher sensitivity for the clinical report. This supports the clinical practice, which favored overestimation of difficult to quantify stenoses.